Political connections and seasoned equity offerings - Nnadi, Modestus I.; Sorwar, Ghulam; Eskandari, Rasol; Chizema, Amon (Journal of Banking & Finance, 2021)
This study examines the impact of political connections on seasoned equity offerings. Using seasoned equity offerings (SEOs) from 2001 to 2018 in the USA, we find that politically connected issuers enjoy a lower cost of seasoned equity issuance than their non-connected counterparts. Our empirical evidence is robust to controls for firm characteristics, corporate governance features, propensity score matching models, and an instrumental variable approach. Moreover, connected issuers conducting primary offerings and those operating in high corrupt states benefitted more from their political connections. Overall, our evidence is consistent with the view that political connections reduce the cost of raising external capital.